Pajak Parkir Rumahan: Potensi Pendapatan Asli Daerah yang Dipandang “Sebelah Mata” - Faridah Inayati; Achdiar Redi Setiawan; Nurul Herawati (Prodi Akuntansi - FEB Universitas Muhammadiyah Gresik, 2019)
The purpose of this study to search, explore, unravel the reality and the awareness of the business tax payer home park in Sidoarjo. The research approach used qualitative research method of phenomenology. Qualitative method was chosen since this study need intensive effort to explore the reality. The informant of this research consist of the tax authorities and business owners. The results of this study indicate that business owners whose a resident parking as Perda No. 8 Tahun 2011 about parking didn’t know well that the bussines is the object of the parking tax and have obligation to pay such taxes. Beside it, the tax authorities which are extension agents and tax inspectors will also underestimate the bussines from this sector looked have not worked optimally regarding socialization.